PENGARUH TAX AVOIDANCE DAN KINERJA LINGKUNGAN TERHADAP SUSTAINABILITY REPORT DISCLOSURE - Lestari, Clarisa Bunga; Januarsi, Yeni; Soerono, Ayu Noorida (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to determine the effect of tax avoidance and environmental performance on sustainability report disclosure. This study uses stakeholder theory to explain the problem. The population in this study was conducted on energy and raw material sector companies listed on the IDX in 2021-2023. The sampling technique used in this study was the purposive sampling method with a sample size of 60 companies. The data analysis technique for this study used ordinary least squares regression collected in a cross-sectional time-series with standard error clustered by firm and Year, with STATA v14.2 software. The results of the study indicate that tax avoidance has a negative effect on sustainability report disclosure, and environmental performance has a positive effect on sustainability report disclosure in energy and raw material sector companies listed on the IDX in 2021-2023.